1998
DOI: 10.2307/4003409
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Habitat Selection by Sage Grouse in South-Central Washington

Abstract: To characterize western sage grouse (Cenkocercus urophusiunus phubs Bonaparte) nesting habitat in sagebrush-steppe habitat in Washington, we iuitiated a study on the Yakima Trahdng Center to determine nesting habitat characteristics and whether these characteristics diiered between successful and depredated nests. Most nests (71%) were in big sagebrush (Artemesia trkfenfafu Nutt.)/bunchgrass communities. Nest habitat was characterized by greater shrub cover, shrub height, vertical cover height, residual cover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
142
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(163 citation statements)
references
References 11 publications
15
142
6
Order By: Relevance
“…al 1989a. Females typically start visiting leks in early to mid-March in Washington (Sveum 1995, Oregon , and lowland populations of Idaho (Idaho Department of Fish and Game, unpublished data), midto late March in Montana , California (Bradbury et al 1989a), and mountain valley populations of Idaho (Idaho Department of Fish and Game, unpublished data), and late March to early April in Alberta (Aldridge 2000), Colorado (Petersen 1980, and Wyoming . Peak hen attendance is typically mid-to late March in Washington , late March to early April in California (Bradbury et al 1989a), Oregon , and lowland populations of Idaho (Idaho Department of Fish and Game, unpublished data), early April in Alberta (Aldridge and Brigham 2001), Moffat County Colorado , and Montana , and early to mid-April in Wyoming , North and Middle Park Colorado (Petersen 1980, and mountain valley populations of Idaho (Idaho Department of Fish and Game, unpublished data).…”
Section: Timing Of Breeding Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…al 1989a. Females typically start visiting leks in early to mid-March in Washington (Sveum 1995, Oregon , and lowland populations of Idaho (Idaho Department of Fish and Game, unpublished data), midto late March in Montana , California (Bradbury et al 1989a), and mountain valley populations of Idaho (Idaho Department of Fish and Game, unpublished data), and late March to early April in Alberta (Aldridge 2000), Colorado (Petersen 1980, and Wyoming . Peak hen attendance is typically mid-to late March in Washington , late March to early April in California (Bradbury et al 1989a), Oregon , and lowland populations of Idaho (Idaho Department of Fish and Game, unpublished data), early April in Alberta (Aldridge and Brigham 2001), Moffat County Colorado , and Montana , and early to mid-April in Wyoming , North and Middle Park Colorado (Petersen 1980, and mountain valley populations of Idaho (Idaho Department of Fish and Game, unpublished data).…”
Section: Timing Of Breeding Behaviormentioning
confidence: 99%
“…Numerous studies have reported on characteristics of greater sage-grouse (Centrocercus urophasianus) populations and habitats throughout the species' range , Sveum et al 1998, Commons et al 1999, and others). Additionally, provided guidelines for managing sage-grouse populations and habitats and identified monitoring as an important component of a sage-grouse management program.…”
Section: Introductionmentioning
confidence: 99%
“…In south-central Washington, 66 -71% of sage-grouse nests were under big sagebrush although big sagebrush made up only 46% of the available habitat (Sveum et al 1998). In Oregon, sage-grouse nest success was highest in mountain big sagebrush A. tridentata vaseyana (Gregg 1991).…”
mentioning
confidence: 99%
“…In southeastern Idaho, 78% of sage-grouse nests were under threetip sagebrush in an area dominated by this shrub (Klebenow 1969). Nevertheless, no study has yet assessed sage-grouse use of threetip sagebrush or compared the reproductive performance of sagegrouse using threetip sagebrush vs big sagebrush as nest canopy cover (Klebenow 1969, Sveum et al 1998. Understanding sage-grouse use of threetip sagebrush in relation to other sagebrush species will expand our understanding of sage-grouse reproduction in threetip sagebrush dominated landscapes, and increase our ability to predict how sage-grouse will respond to fire and other disturbances that result in threetip sagebrush replacing big sagebrush.…”
mentioning
confidence: 99%
See 1 more Smart Citation